Beyond Access: Empowering Algerian Students in Online Learning Through Digital Literacy and a Pedagogy of Abundance - Dallel Sarnou (EDUTREND: Journal of Emerging Issues and Trends in Education, 2024)
This research investigated how the rapid shift to online learning platforms in Algerian universities has exposed a critical gap in students' digital dexterity skills. It aimed at exploring students' weaknesses in navigating limitless online resources. Data from a survey administered to 150 students and interviews with 12 university teachers disclosed key areas where students struggle. The findings revealed that in spite of the recent blossoming of online education in Algeria, our students still experience major weaknesses regarding digital dexterity. Also, the findings highlight the need to move towards a pedagogy of abundance to equip students with the skills to access information and to critically evaluate online content. Empowering teachers to integrate digital literacy development within their teaching practices is another crucial action to take so as to bridge the digital dexterity gap and ensure students can thrive in this information-rich online learning environment.